PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN (STUDI PADA SEKTOR PERTAMBANGAN DI BURSA EFEK INDONESIA) - Budi - Setyawan (Universitas Pamulang, 2017)
Abstract This study aims to analyze the influence of Corporate Social Responsibility and Good Corporate Governance (independent commissioner, number of directors and number of audit committees) on the value of the company in the mining issuer in Indonesia Stock Exchange. Research samples of 20 companies and years of research that is 2011 - 2015. The data collected is processed by simple and multiple regression. The result of research shows that there is no influence of Corporate Social Responsibility to Corporate Value. The effect of independent commissioners on corporate value is insignificant. The effect of the number of directors on firm value is significant. The influence of audit committees on corporate value is not significant. Simultaneously CSR, independent commissioner, number of directors and number of audit committee have an effect on signifikan to Company Value. The magnitude of Corporate Social Responsibility and Good Corporate Governance (Independent Commissioner, Number of Directors and Audit Committee) to the dependent variable of Corporate Value has a coefficient of determination of 0.049 indicating that the contribution of Corporate Social Responsibility and Good Corporate Governance of Independent Commissioners, Number of Directors, and Audit Committee) together against Corporate Value is 4.9%, the rest is caused by other factors. Keywords : Corporate Social Responsibility, Good Corporate Governance, Corporate Value